2013
DOI: 10.1186/1743-422x-10-105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38MAPK and CD137 signaling reduce dengue virus-induced TNF-α secretion and apoptosis

Abstract: BackgroundHepatic injury in dengue virus (DENV) infection is authenticated by hepatomegaly and an upsurge in transaminase levels. DENV replicates in hepatocytes and causes hepatocyte apoptosis both in vitro and in vivo. Understanding the molecular mechanisms of DENV-induced hepatic injury could facilitate the development of alternate chemotherapeutic agents and improved therapies.FindingsThe p38 mitogen-activated protein kinase (MAPK) participates in both apoptosis-related signaling and pro- inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Transaminase levels are increased in DENV-infected patients (Halstead, 1988;Kuo et al, 1992;Souza et al, 2004) and in a murine model of DENV infection (Barth et al, 2006;Chen et al, 2004;Franca et al, 2010;Paes et al, 2005Paes et al, , 2009). Apoptosis of hepatic cells, which may be related to the pathogenesis of DSS, has been observed both in vitro and in vivo (Couvelard et al, 1999;El-Bacha et al, 2007;Huerre et al, 2001;Limonta et al, 2007;Lin et al, 2008;Marianneau et al, 1998;Morchang et al, 2011;Nagila et al, 2011Nagila et al, , 2013Netsawang et al, 2010;Thongtan et al, 2004). DENV infection promotes apoptosis in the hepatoma cell line, HepG2, partly through the induction of TRAIL, a member of the death receptor pathway (Matsuda et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Transaminase levels are increased in DENV-infected patients (Halstead, 1988;Kuo et al, 1992;Souza et al, 2004) and in a murine model of DENV infection (Barth et al, 2006;Chen et al, 2004;Franca et al, 2010;Paes et al, 2005Paes et al, , 2009). Apoptosis of hepatic cells, which may be related to the pathogenesis of DSS, has been observed both in vitro and in vivo (Couvelard et al, 1999;El-Bacha et al, 2007;Huerre et al, 2001;Limonta et al, 2007;Lin et al, 2008;Marianneau et al, 1998;Morchang et al, 2011;Nagila et al, 2011Nagila et al, , 2013Netsawang et al, 2010;Thongtan et al, 2004). DENV infection promotes apoptosis in the hepatoma cell line, HepG2, partly through the induction of TRAIL, a member of the death receptor pathway (Matsuda et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…DENV infection promotes apoptosis in the hepatoma cell line, HepG2, partly through the induction of TRAIL, a member of the death receptor pathway (Matsuda et al, 2005). TNF-␣ and Fas signaling also contribute to DENV-mediated apoptosis (Limjindaporn et al, 2007;Nagila et al, 2013). The mitochondria of DENV-infected HepG2 cells exhibit functional and morphological defects, suggesting activation of the mitochondrial cell death pathway (El-Bacha et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we detected slightly more 282 viruses in the SB203580 treated animals compared to control AG129 mice. Recently, p38 MAPK inhibition has been described 284 to limit the apoptosis of infected cells(Nagila et al, 2013). In that285 context, delaying apoptosis or inflammation in vivo may favor 286 more viruses to be produced after 5 days of therapy.…”
mentioning
confidence: 99%
“…[21] Although it has been demonstrated that HIF1α-related TNFRSF9 upregulation is beneficial for the survival of hematopoietic cells, it can induce cellular apoptosis in other cell types such as liver or tumor cells. [22][23][24] This might at least partly explain why severe liver toxicity occurred in the first clinical studies targeting TNFRSF9 in humans. [25] Whether enhanced TNFRSF9 expression in perinecrotic areas in melanoma brain metastasis is beneficial or detrimental to the tumor remains an open question.…”
Section: Discussionmentioning
confidence: 99%